Combined strengthening from nanotwins and nanoprecipitates in an iron-based superalloy. (1st June 2018) - Zhang, B.B.; Yan, F.K.; Zhao, M.J.; Tao, N.R.; Lu, K.
Abstract: A bulk nanostructured solutionized iron-based superalloy consisting of nanotwins and dislocation structures was prepared by means of dynamic plastic deformation at a high strain rate. The nanotwins constitute ∼51% in volume with the average twin/matrix lamella thickness of ∼20 nm. The sample exhibits a yield strength as high as 1130 MPa but with nearly zero uniform elongation. Subsequent peak-aging treatment at 700 °C for 1 h results in the precipitation of nano-sized gamma prime phases with a random distribution in the nanotwins and deformed matrix. The nanotwins still remain and keep the corresponding strengthening after aging. Those dispersed nanoprecipitates further raise the strength of the aged sample to 1420 MPa. Meanwhile, the uniform elongation increases to ∼3% due to the intrinsic plasticity of nanotwins with a reduced dislocation density after aging annealing. This kind of combined strengthening from both nanotwins and precipitates provides a new strategy to further raise the strength of nanotwinned materials or precipitation-strengthened materials. Graphical abstract: Image 1